MAKNA MANUHIR DALAM KEHIDUPAN MASYARAKAT DAYAK NGAJU DI KOTA PALANGKA RAYA - Desi Natalia; Jefry Tarantang; Ni Nyoman Adi Astiti (Jurnal Studi Agama dan Masyarakat, 2020)
It was known that Dayak people as well as other tribes had its own norms and laws,  known as Hadat  in every activity and situation. This was also performed by Ngaju Dayak society in discarding a hunch, namely manuhir. Manuhir is an alternative healing carried out by Ngaju Dayak people in ancient times to get rid of the hunches within. This paper attempted to describe Manuhir custom in the view of Ngaju Dayak people at Palangka Raya, Central Kalimantan. In addition, it was also  to maintain manuhir as an alternative healing carried out by Ngaju Dayak people as an identity of Dayak Ngaju people, so that the meaning of this ritual did not face obscurity in the future. The implementation of  muhuhir action indicated the obidience of  Dayak Ngaju people in their customs and traditions, since this activity was a mandatory for those who have such hunches.